Psychoanalysis, Artistic Obsession, and Artistic Motivation: The Study of Pathography. Issue 1 (February 2014) - Kemler, David S.
A modern assessment of Freud's conceptualization of the creative process focusing on drives, ego psychology, and object relation theory is presented. 40 artists and musicians were interviewed employing 13 open-ended questions to provoke responses historically associated with the theoretical conceptualizations of Freud and post-Freudian theory related to the creative process. Creative process was defined as internal object relations that motivate the external connection between artist and the creative work. Measured responses concerning purpose and understanding; motivation before, during, and after performance; obstacles in performance; and needs through the creative process were assessed. Cluster analysis segregated the participants into high, medium, and low agreement groups based on similarity of responses. A multivariate stepwise regression revealed four questions (enlightenment, drives, obstacles, and ought self discrepancies) accounted for 83.9% of the variance. A post hoc discriminant function analysis identified 82.5% of the population to their correct groups. The findings support Spitz's (2005) suggestion that we regard "drives, ego psychology, and object relation theory not as separate approaches but as parts of a whole with varying stresses or accents" (p. 503).